2018
DOI: 10.2169/internalmedicine.9222-17
|View full text |Cite
|
Sign up to set email alerts
|

Useful Predictive Factors for Bacteremia among Outpatients with Pyelonephritis

Abstract: Objective The aim of this study was to identify predictive factors for bacteremia conveniently and quickly among outpatients diagnosed with pyelonephritis. Patients All patients who were diagnosed with pyelonephritis at the outpatient clinic in the Department of General Medicine of Juntendo University Hospital from April 1, 2008, to June 30, 2015, were enrolled. Patients from whom blood cultures had not been taken were excluded. Methods Clinical information was extracted from medical charts. Factors potentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…This was regardless of the presence or absence of a positive leucocyte test. Similar results were obtained in an adult study 11 …”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This was regardless of the presence or absence of a positive leucocyte test. Similar results were obtained in an adult study 11 …”
Section: Discussionsupporting
confidence: 90%
“…Similar results were obtained in an adult study. 11 UTI is the most common serious bacterial infection in febrile young infants. 1,2 A definitive diagnosis of UTI is based on a positive urine culture result.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 7 Furthermore, other preliminary research has indicated that older age, positive urinary nitrite test results, and chills tend to be seen in patients with pyelonephritis accompanied by bacteremia. 8 However, the quick Sequential Organ Failure Assessment (qSOFA), which is now widely used, was not incorporated as part of this preliminary research. 9 Furthermore, a score classification system for recommendation of hospitalization does not exist for patients with pyelonephritis, in contrast to our experience with other diseases (e.g., CURB-65 for patients with pneumonia).…”
Section: Introductionmentioning
confidence: 99%